Association between the frequency of different modes of delivery and depression: a national cross-sectional study - He, Sijie; Li, Houhong; Xie, Fan; Li, Wei; Wan, Li; Zhang, Huan (Frontiers in Psychiatry, 2025)
BackgroundDepression is a significant mental health concern among women. The objective of this study was to explore the relationship between reproductive factors such as parity and the frequency of different modes of delivery and depression.MethodsThe analysis was conducted based on the National Health and Nutrition Examination Survey (NHANES) 2005-2014, involving 5,401 non-pregnant women aged 20 years or older. Depression was evaluated using the Patient Health Questionnaire-9 (PHQ-9), while information on parity and delivery modes was self-reported. Multivariable logistic regression models were employed to investigate the association between parity, the frequency of vaginal and cesarean deliveries, and depression. Additionally, smooth curve fitting and subgroup analysis were performed.ResultsAfter adjusting for all covariates, higher parity (OR: 1.12, 95% CI: 1.06-1.19) and an increased frequency of vaginal deliveries (OR: 1.12, 95% CI: 1.06-1.18) were both associated with a higher prevalence of depression. Women with four or more total births exhibited a 1.78-fold greater prevalence of depression relative to those with no births. Similarly, compared to women with no vaginal deliveries or cesarean sections, the prevalence was 1.81 times higher in those with four or more vaginal deliveries and 2.03 times higher in those with four or more cesarean deliveries.ConclusionsGreater parity, particularly a higher frequency vaginal deliveries, is significantly associated to an elevated prevalence of depression among women. The findings highlight the need to consider reproductive history in mental screening for women, especially those with multiple vaginal deliveries.